Meningkatkan Kemampuan Peserta Didik dalam Pembelajaran Bahasa Arab Terhadap Maharah Al-Kitabah dengan Metode Pembelajaran Insya’iyah - Dea Adinda; Era Fazira; Rafly Syahputra Sikumbang; Sahkholid Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Apart from be.ing famous for the language of the Koran, Arabic has an important role in entering the current era of globalization, moreover Arabic is also an international language that we should have mastered. Therefore, Arabic has been widely studied in several schools, especially in Islamic educational institutions or Islamic-based schools. To make it easier for educators to convey Arabic language learning, educators should master the methods used in learning Arabic. In this writing, the author will explain a method for learning Arabic, especially the Maharah Al-Kitabah, to make it easier for educators to achieve learning goals. The method for learning Arabic in Maharah Al-Kitabah which will be discussed in this writing is the insyaiyah method. The purpose of this writing is to make it easier for educators or anyone who reads this article to inform and make it easier to choose Arabic language learning methods. The author uses the library research method, namely a series of activities relating to library data collection methods, by collecting as much data as possible through books, journals, the internet and so on, then criticizing and writing it into this paper when he has found it. accurate data.